1993
DOI: 10.1172/jci116715
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally high thromboxane biosynthesis in homozygous homocystinuria. Evidence for platelet involvement and probucol-sensitive mechanism.

Abstract: IntroductionHomocystinuria due to homozygous cystathionine tl-synthase deficiency is an inborn error of metabolism characterized by a high incidence of thrombosis and premature atherosclerosis. We evaluated TXA2 biosynthesis in vivo and several in vitro tests of platelet function in 11 homocystinuric patients and 12 healthy controls. In vitro, patients' platelet aggregation was within control values as were TXB2 formation, fibrinogen binding, and ATP secretion in response to thrombin. In contrast, the urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(82 citation statements)
references
References 44 publications
(53 reference statements)
5
75
1
1
Order By: Relevance
“…In HHcy patients, increased platelet activation has been associated with elevated production of tromboxane A 2 (28)(29)(30). In line with these findings, in MTHFR++ carriers, we found that urine thromboxane metabolites were significantly higher than in healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…In HHcy patients, increased platelet activation has been associated with elevated production of tromboxane A 2 (28)(29)(30). In line with these findings, in MTHFR++ carriers, we found that urine thromboxane metabolites were significantly higher than in healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…Methionine-loading experiments in control and folate-deficient animals indicated that homocysteine plasma concentration correlates with platelet aggregation and the biosynthesis of the powerful proaggregant thromboxane A 2 (Durand et al, 1997a). In agreement with this latter finding, an increase in thromboxane synthesis was described in homocystinuric patients (Di Minno et al, 1993). Along with a possible reduction of the antiplatelet effects of NO, this increase in thromboxane biosynthesis might contribute to platelet activation in moderate hyperhomocysteinemia (Durand et al, 1997a).…”
Section: Alterations Of Vascular Thromboresistancementioning
confidence: 64%
“…Thus, it is likely that the flow-induced arteriolar release of TXA 2 together with that released from platelets 11 contributes to the development of increased vascular tone and urinary excretion of TXB 2 , the stable end metabolite of TXA 2 shown to be present in patients with genetic HHcy. 29,30 The underlying mechanism for the simultaneous impaired NO release and enhanced TXA 2 production in the endothelium of arterioles of HHcy rats 10,11 is not known. Several previous studies in endothelial cells in culture 31,32 suggest a role for an increased level of reactive oxygen species (ROS).…”
Section: February 2001mentioning
confidence: 99%